CARDIOVASCULAR EFFECTS OF CENTRAL CLONIDINE IN CONSCIOUS RATS AFTER HYPOTHALAMIC-LESIONS - Colombari, Eduardo [UNESP]; Camargo, LAD; Saad, W. A.; Renzi, Antonio [UNESP]; Deluca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1992)
The central injection of clonidine (an alpha-2-adrenoceptor agonist) in conscious normotensive rats produces hypertensive responses and bradycardia. The present study was performed to investigate the effect of electrolytic lesions in the anteroventral third ventricle (AV3V) region or in the lateral hypothalamus (LH) on the pressor and bradycardic responses induced by central clonidine in rats. Mean arterial pressure and heart rate were recorded in sham or AV3V-lesioned rats with cerebral stainless steel cannulae implanted into the lateral cerebral ventricle (ICV) or LH. and in sham or bilateral LH-lesioned rats with cannulae-implanted ICV. The injection of clonidine (40 nmol) ICV or into the LH of sham rats produced a pressor response (37 +/- 2-48 +/- 3 mmHg) and bradycardia (-45 +/- 10--93 +/- 6 bpm). After AV3V-lesion (3 and 12 days) or LH-lesion (3 days) the pressor response was abolished and a small hypotensive response was induced by the injection of clonidine (-1 +/- 3--16 +/- 3 mmHg). The bradycardia (-27 +/- 6--57 +/- 11 bpm) was reduced, but not abolished by the lesions. These results show that the AV3V region and LH are important cerebral structures that participate in the excitatory pathways involved in the pressor response to central clonidine in rats. They also suggest that, in the absence of these pressor pathways, the hypotensive responses to central clonidine may appear in conscious rats.
Keywords: AV3V REGION; LATERAL HYPOTHALAMUS; ARTERIAL PRESSURE; CENTRAL ADRENERGIC PATHWAY